“Los principios del Sistema Nacional de Contratación Pública y su incidencia en los procesos de subasta inversa electrónica de la Universidad Nacional de Chimborazo durante el año 2014” - Arévalo Lara, Diana Carolina (2016)
For purchasing goods and services, the Ecuadorian state and its public institutions used to hire them by using a very slow procedure which took them too much time. Consequently, the Ecuadorian state decided to create a law in order to apply a dynamic purchasing procedure; it is called electronic reverse auction which includes an electronic catalog for purchases. Then, goods and services buying procedures would be carried out in an efficient way and deliver a better service. The mentioned procedures have allowed to reach a high procurement level which means a significant public saving, for the general Ecuadorian budget. Also, they have benefited small and medium businesses mostly, including those which belong to popular and solidarity economy businesses. In other words, the aim of the Ecuadorian state is to provide a digital access through a platform for purchasing goods and services. All public institutions must use it in order to purchasing/hiring goods and services. Therefore, public purchasing/ hiring on line is a fascinating and relevant topic, since electronic reverse auction for goods and services procurement has become a very popular procedure by governmental institutions. It provides a great deal of benefits which will be studied through this field research.